FAULT ANALYSIS ON AN INTERCONNECTED POWER SYSTEMNETWORK USING POWER SYSTEM STABILIZER - ARAGA, IDRIS; AIROBOMAN, ABEL; FAHIM, IRENE (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
In this study, the fault responses on power system networks, the impact of power system stabilizers on current as well as bus voltages on machines and affected buses in the Nigerian Grid System (NGS) and the IEEE 9-bus network was considered. In order to achieve this aim, load flow analyses was carried along the network to determine the natural flow of power thereafter, codes were written on the MATLAB environment to analyze the effect of three-phase faults along the network at various buses. The results from the study show that the system loss synchronism and was therefore unstable at the occurrence of a three phase short circuit fault without the presence of PSS. For stability of the network to be regained therefore, it was observed that faults of this type should be cleared within the first 0.16s. It was also shown that prior to introducing supplementary control in the form of PSS; the system was unstable but regained stability within 4-10s after the incorporation of PSS.Conclusively, the mean percentage deviation or change for current and voltage at the IEEE 9-bus system are 11.1 and 53.4 respectively. For the NGS, the average percentage current and voltage change in values are 29.4 and 11.8 respectively. The nonlinear simulations are presented for the selected power systems to validate the increased damping of currents and voltages experienced by application of Power System Stabilizers (PSS) to some selected buses with high oscillations was pronounced within 5s of fault clearing establishing enhanced power system dynamic.